NAD Kinases: Metabolic Targets Controlling Redox Co-enzymes and Reducing Power Partitioning in Plant Stress and Development - Li, Bin-Bin; Wang, Xiang; Tai, Li; Ma, Tian-Tian; Shalmani, Abdullah; Liu, Wen-Ting; Li, Wen-Qiang; Chen, Kun-Ming (Frontiers in Plant Science, 2018)
NAD(H) and NADP(H) are essential co-enzymes which dominantly control a number of fundamental biological processes by acting as reducing power and maintaining the intracellular redox balance of all life kingdoms. As the only enzymes that catalyze NAD(H) and ATP to synthesize NADP(H), NAD Kinases (NADKs) participate in many essential metabolic reactions, redox sensitive regulation, photosynthesis performance and also reactive oxygen species (ROS) homeostasis of cells and therefore, play crucial roles in both development and stress responses of plants. NADKs are highly conserved enzymes in amino acid sequences but have multiple subcellular localization and diverse functions. They may function as monomers, dimers or multimers in cells but the enzymatic properties in plants are not well elucidated yet. The activity of plant NADK is regulated by calcium/calmodulin and plays crucial roles in photosynthesis and redox co-enzyme control. NADK genes are expressed in almost all tissues and developmental stages of plants with specificity for different members. Their transcripts can be greatly stimulated by a number of environmental factors such as pathogenic attacks, irritant applications and abiotic stress treatments. Using transgenic approaches, several studies have shown that NADKs are involved in chlorophyll synthesis, photosynthetic efficiency, oxidative stress protection, hormone metabolism and signaling regulation, and therefore contribute to the growth regulation and stress tolerance of plants. In this review, the enzymatic properties and functional mechanisms of plant NADKs are thoroughly investigated based on literature and database. The results obtained here are greatly advantageous for further exploration of plant NADKs functions.